Research on Wireless Charging Device EMC Testing - Ruichen Xu; Qizhu Song; Junfeng Wang; Xiaoyong Liu; Xiao Peng; Ji Fang (Dianxin kexue)
The current technical approaches of wireless charging devices and international existing wireless charging standard were analyzed. Then, the electromagnetic compatibility for wireless charging case management in Europe, America, Korea and Japan was discussed and explored. Hereafter, the domestic classification methods and testing standards of information technology equipment, short-range radio devices and ISM equipment were researched. Finally, the following wireless charging devices electromagnetic compatibility testing proposals were obtained:wireless charging equipment classification attribution recommendation in domestic existing testing standard, domestic wireless charging device electromagnetic testing methods recommendation, wireless charging device management recommendations.